La (ri)scoperta dell’identità attraverso il calcio: l’onda azzurra, il caso dei tifosi del Napoli che vivono in Europa - Rossano, Marco (Eracle. Journal of Sport and Social Sciences, 2018)
Football is one of the most important social phenomena of the 20th and 21st centuries. It can be regarded as a kaleidoscope of human emotions, a stage from which to observe and study social reality. In the development of identity, sports are a means through which to create “Us” and “Them”. Football goes beyond the mere sporting field and through identification with a team, people can express their own identification with something that goes beyond sports: city, region, specific subgroup, social class or ethnic group. In this paper I use qualitative research methods and audio-visual techniques to analyse the case of football fans of Naples Football team living in Barcelona. Within the migratory experience, many Neapolitans consider football as an additional component to maintain a close link with their own origins. Football allows them to feed the sense of belonging and (re)discover old and new identity elements.